2013
DOI: 10.1080/13613324.2013.832917
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue Race Ethnicity and Education: Initial teacher education: developments, dilemmas and challenges

Abstract: dilemmas and challenges IntroductionVini Lander University of Chichester v.lander@chi.ac.ukThe education of new teachers is a fundamental aspect of education provision within any country in the world. The education of pre-service teachers is known to have a direct impact on the outcomes for children in our schools. In England, teacher education within universities has been subject to erosion with the introduction of more school-based training and greater scrutiny by the government inspection agency, the Office… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…For TOCs who gain entrance into a preservice program at a predominately White institution, they encounter a number of additional obstacles as prevailing ideologies of whiteness permeate and inform the work of school. These include, but are not limited to, experiences with overt and covert racism (Jones & Maguire, 1998;Kohli, 2009); linguicism (Lippi-Green, 1997); stereotyping (Cole & Stuart, 2005;Griffin, 2018); microaggressions (Endo, 2015); color-blindness (Johnson, 2002); being rendered the professional "Other" (being viewed as a cultural expert) (Santoro, 2015); homogenizing racial and ethnic groups (Lander, 2014); lack of support within the faculty (Cho, 2013); a perception that ethnic and racial diversity is sought by employers and as such racialized teachers are "taking" the jobs of the dominant group (Ryan, Pollock, & Antonelli, 2009); and an assumption of a level playing-field (Coates, 2010). Some of the toxic environmental conditions that teacher candidates of Color experience continue in their inservice work experiences, thus contributing to retention challenges.…”
Section: Recruitment and Retention Challenges: Keeping Out Teachers Of Colormentioning
confidence: 99%
“…For TOCs who gain entrance into a preservice program at a predominately White institution, they encounter a number of additional obstacles as prevailing ideologies of whiteness permeate and inform the work of school. These include, but are not limited to, experiences with overt and covert racism (Jones & Maguire, 1998;Kohli, 2009); linguicism (Lippi-Green, 1997); stereotyping (Cole & Stuart, 2005;Griffin, 2018); microaggressions (Endo, 2015); color-blindness (Johnson, 2002); being rendered the professional "Other" (being viewed as a cultural expert) (Santoro, 2015); homogenizing racial and ethnic groups (Lander, 2014); lack of support within the faculty (Cho, 2013); a perception that ethnic and racial diversity is sought by employers and as such racialized teachers are "taking" the jobs of the dominant group (Ryan, Pollock, & Antonelli, 2009); and an assumption of a level playing-field (Coates, 2010). Some of the toxic environmental conditions that teacher candidates of Color experience continue in their inservice work experiences, thus contributing to retention challenges.…”
Section: Recruitment and Retention Challenges: Keeping Out Teachers Of Colormentioning
confidence: 99%
“…There are similarities between these local descriptions and the national summary offered by Elton-Chalcraft et al (2017, 31): a 'model of Britishness [that is] fearful of strangers, under siege and unsure of itself'. These demographics exacerbate what has been suggested -both nationally and internationally -to be an issue for teacher education programmes (Edgeworth and Santoro 2015;Bhopal and Rhamie 2014;Lander 2014Lander , 2011Larzen-Ostermark 2009;Mills 2009;Allard 2006;Ambe 2006;Clarke and Drudy 2006;Milner et al 2003;Ball 2000;Larke 1990), which 'have been found to be increasingly homogenousprimarily White, middle class and from the dominant culture' (Acquah and Commins 2013, 445). As Milner (2012) suggests, 'it is difficult to have a conversation about discrimination in urban education when those participating have never experienced discrimination themselves' (p.704).…”
Section: Context and Backgroundmentioning
confidence: 97%
“…There may be in-school variance as well as school-to-school variance based on ‘race'. A large corpus of the literature evidences the role ‘race' plays in spaces, organisations, and in a majority White teaching profession (see, Callender (2020); Allen and Liou (2018); Picower and Kohli (2017); Lander and Santoro (2017); Miller (2016); Matias et al (2014); Lander (2014); Picower (2009); Ahmed (2007); Puwar (2004)) for further exploration about how majority teachers' understanding of ‘race' affects interactions and outcomes in schools.…”
Section: Uk Policy Comparisonsmentioning
confidence: 99%